The burden of war-injury in the Palestinian health care sector in Gaza Strip - Marwan Mosleh; Koustuv Dalal; Yousef Aljeesh; Leif Svanström (BMC, 2018)
Abstract Background War-related injury is a major public health concern, and a leading cause of mortality, morbidity, and disability globally, particularly in low and middle-income countries such as Palestine. Little is known about the burden of war-related injury in the Palestinian context. The objective of this study was to characterize the incidence and pattern of injuries, associated with war in Gaza Strip, from July 8 to August 26, 2014. Methods This was a descriptive study based on an injury registry at hospital facilities in the Gaza Strip. A total of 420 victims records from 2014 Gaza war injuries were randomly selected, proportionate to the size of the study population estimated across five Gaza governorates. Simple descriptive statistics were calculated to explore the frequency and percentage distribution of study variables and injury data. A chi-square test (X2) was used. The significance level was derived at p < 0.05. The data were analyzed by IBM SPSS software, version 23. Results Males (75.5%) have experienced more war-related injuries than females (24.5%), constituting a male: female ratio of 3.1:1. Almost half (49.5%) of the injured victims were of the age group 20-39, followed by children and adolescents (< 20 years), accounting for 31.4%. More than half of victims were single (53.6%), 44.3% were married and the rest were widowed or divorced. The overall number of injuries was 6.4 per 1000 population, though it varied among regions. North Gaza reported the highest number of injuries (9.0) and Rafah the lowest (4.7) per 1000 population. Blast and explosion were found to be the most common causes of war injuries (72.9%). The highest proportion of injuries were reported in the upper body. Multiple body shrapnel wounds and burns (39.3%) were most frequent. Other types of injuries were multiple organ injury (24.3%), fractures (13.6%), internal organ injury and bleeding (9.8%), amputation (4.5%), abrasions/lacerations and contusions (4.8%), vision or hearing loss or both (1.9%) and respiratory problems (1.9%). The highest percentage of injuries were classified as mild (46.9%), and the rest ranged from moderate-to-severe. Almost 26% of individuals had sustained disability, and most of them had physical/motor impairment. Conclusion War-related injuries constitute a major problem to public health discipline and clinical medicine as well. A better surveillance system using ICD codes, and development of a comprehensive electronic data network are necessary to make future research easier and more timely.